Contemporary Discourse On Science and Theological Studies Contemporary Between Science And Theology) - Marde Christian Stenly Mawikere; Sudiria Hura (Conference Series, 2020)
This article highlights the “Contribution of Science in Theology”. A contemporary discourse that will briefly describe the general description of “The Essence of Science and Its Purpose” and “Theology and Dynamics”, then formulates the possibilities for the contribution of Science to Theology, or vice versa. This article is not a comprehensive description, but it is an article that will give a concise and concise review of the intended topic. The presupposition of the topic discussed can be formulated briefly that science contributes to developing the “adventure” of theological education. The process of gaining satisfaction in the world of theology is obtained in the same way as the process of acquiring science, namely: First, Starting with confidence and continuing by looking for supporting arguments (a priori). The Bible is the primary and absolute source, while tradition, literature, historical studies and experiments are complementary. Second, start with doubt and continue by looking for evidence of its justification (a posteriori). Primary and secondary sources are the same as above. Both of the above will not be discussed at length in this article, but will be described in such a way that eventually the reader will get an initial prediction that “science and theology” never “duel” each other but can be “mutual”, as well as “dialogue”.